Antecedents of Brand Hate and the Role of Brand Recovery towards Brand Reconciliation in the Pakistani Fast Food Industry - Sheraz, Ahmed (2019)
Brand hate is an extreme negative emotion developed in the consumers of a brand when they perceive the brand as inappropriate due to various reasons. Brand hate have been known to cause great harm to the companies and their brands. Companies face negative consequences from the brand haters such as negative word of mouth, brand rejections, brand boycotts, and anti-branding activities. This study has investigated the concept of brand hate in the light of the theory of hate and the theory of consumer brand relationship. The objectives of this study are to investigate whether the direct personal antecedents(negative past experience, symbolic incongruity, and poor relationship quality) and indirect non-personal antecedents (ideological incompatibility and rumor) triggers brand hate among consumers or not. Moreover, to investigate whether the elements of brand recovery process (apology, compensation, and explanation) helps in minimizing brand hate or not. For the purpose of testing these objectives, experiments were performed on 250 fast food brand consumers in Pakistan in the form of groups using independent group design. Results from partial least square structural equation modeling (PLS-SEM) confirmed that negative past experience, symbolic incongruity, poor relationship quality, ideological incompatibility, and rumor helps in the development of brand hate among consumers. Rumor was found to be the biggest instigator of brand hate. Moreover, the results of the multi-group analysis (PLS-MGA) showed that the categorical moderator of brand recovery helps in minimizing brand hate. Among the group comparisons that were performed in multi-group analysis (PLS-MGA), the most effective of all the group interventions to minimize brand hate was the combination of apology, compensation, and explanation. The group of respondents that received ‘compensation’ as an intervention was the second most significant group in managing brand hate, the group that received ‘apology’ as an intervention was the third significant group in minimizing brand hate. Further the group that received ‘explanation’ as a recovery strategy failed to minimize brand hate significantly. The last group which is known as the control group where no intervention was applied, the intensity of brand hate was increased among the participants of that group, and therefore there was significant difference between control group with no intervention and all other groups with different interventions. These findings are consistent with the propositions of the theory of hate and the theory of consumer brand relationship where it was suggested that hate can be instigated not only by direct personal experiences but also from indirect non-personal experiences like ideological beliefs and rumors, and also the quality of relationship lead towards good or bad emotions and behaviors. The theories also proposed that hate can be managed from different strategies such as wisdom, forgiveness, compensations, and various other win-win strategies. Further the theoretical and practical implication are also discussed in this study.